Effectiveness of Cricoid and Paratracheal Pressures in Occluding the Upper Esophagus Through Induction of Anesthesia and Videolaryngoscopy: A Randomized, Crossover Study. (1st August 2022) - Kim, Hyerim; Chang, Jee-Eun; Won, Dongwook; Lee, Jung-Man; Kim, Tae Kyong; Kim, Min Jong; Min, Seong-Won; Hwang, Jin-Young
Abstract : BACKGROUND: Maneuvers for preventing passive regurgitation of gastric contents are applied to effectively occlude the esophagus throughout rapid sequence induction and intubation. The aim of this randomized, crossover study was to investigate the effectiveness of cricoid and paratracheal pressures in occluding the esophagus through induction of anesthesia and videolaryngoscopy. METHODS: After the induction of anesthesia in 40 adult patients, the location of the esophageal entrance relative to the glottis and location of the upper esophagus relative to the trachea at the low paratracheal region were assessed using an ultrasonography, and the outer diameter of the esophagus was measured on ultrasound before and during application of cricoid and paratracheal pressures of 30 N. Then, videolaryngoscopy was performed with the application of each pressure. During videolaryngoscopy, location of the esophageal entrance relative to the glottis under cricoid pressure was examined on the screen of videolaryngoscope, and the upper esophagus under paratracheal pressure was evaluated using ultrasound. The occlusion rate of the esophagus, and the best laryngeal view using the percentage of glottic opening scoring system were also assessed during videolaryngsocopy. Esophageal occlusion under each pressure was determined by inserting an esophageal stethoscope into the esophagus. If the esophageal stethoscope could not be advanced into the esophagus under the application of each pressure, the esophagus was regarded to be occluded. RESULTS: During videolaryngoscopy, esophagus was occluded in 40 of 40 (100%) patients with cricoid pressure and 23 of 40 (58%) patients with paratracheal pressure (difference, 42%; 95% confidence interval, 26–58; P < .001). Both cricoid and paratracheal pressures significantly decreased the diameter of the esophagus compared to no intervention in the anesthetized paralyzed state ( P < .001, respectively). Ultrasound revealed that the compressed esophagus by paratracheal pressure in the anesthetized paralyzed state was partially released during videolaryngoscopy in 17 of 40 patients, in whom esophageal occlusion was unsuccessful. The best laryngeal view was not significantly different among the no intervention, cricoid pressure, and paratracheal pressure (77 [29] % vs 79 [30] % vs 76 [31] %, respectively; P = .064). CONCLUSIONS: The occlusion of the upper esophagus defined by inability to pass an esophageal stethoscope was more effective with cricoid pressure than with paratracheal pressure during videolaryngoscopy, although both cricoid and paratracheal pressures reduced the diameter of the esophagus on ultrasound in an anesthetized paralyzed state.